An Analysis of the Effect of Saturday Home Football Games on Physical Use of University Libraries - Sewell, Kerry (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2021)
Objective – Library science literature lacks studies on the effect of external events on the physical use of libraries, leaving a gap in understanding of would-be library patrons’ time use choices when faced with the option of using the library or attending time-bound, external events. Within academic libraries in about 900 colleges and universities in the US, weekend time use may be affected by football games. This study sought to elucidate the effect of external events on physical use of libraries by examining the effect of Saturday home football games on the physical use of the libraries in a large, academic institution.Methods – This study used a retrospective, observational study design. Gate count data for all Saturdays during the fall semesters of 2013-2018 were collected for the two primary libraries at East Carolina University (main campus’ Academic Library Services [ALS] and Laupus, a health sciences campus library), along with data on the occurrence of home football games. The relationship between gate counts and the occurrence of home football games was assessed using an independent samples t-test.Results – Saturday home football games decreased the gate count at both ALS and Laupus. For ALS, the mean physical use of the library decreased by one third (34.4%) on Saturdays with a home game. For Laupus, physical use of the library decreased by almost a quarter (22%) on Saturdays with a home game.Conclusion – Saturday home football games alter the physical use of academic libraries, decreasing the number of patrons entering the doors. Libraries may be able to adjust staffing based on reduced use of library facilities during these events.